Mengubah Kelemahan Menjadi Kekuatan: Memantik Kepekaan dan Budaya Baru Pengelolaan Sampah pada Kaum Muda - Derajad Sulistyo Widhyharto; Elvin Wahyu Wardhana; Stefanus Fajar Setyawan (Direktorat Pengabdian kepada Masyarakat, 2023)
Ineffective waste management in the Special Region of Yogyakarta, coupled with weak community involvement, has led to protests and the closure of the Integrated Waste Management Facility (TPST). The government is actively seeking solutions by allocating specific land, fostering interregional cooperation, and providing waste sorting facilities for the public. However, waste management appears to be trapped in a vicious cycle due to the neglect of the community's role as a key stakeholder. This article bridges the gap between circular economy knowledge and waste management practices through youth involvement. The Youth Studies Center at Gadjah Mada University collaborates with entities such as Bank Sampah Tinalan, Daur Resik, Sawo Kecik, and DNVB Indonesia, engaging students from SMP Negeri 9 and SMA Negeri 5 in Yogyakarta in a campaign titled